Principles of nasal reconstruction - Baker, Shan R. (Springer, 2011)
Principles of Nasal Reconstruction, Second Edition, is a comprehensive, in-depth resource written by one of the world?s foremost practitioners of nasal reconstruction. This thoroughly revised and updated textbook discusses a wide range of basic and advanced nasal reconstructive procedures in patients presenting with a variety of partial and full thickness defects of the nose. Part One discusses the fundamentals of nasal reconstruction. It provides algorithms to assist the surgeon in selecting the preferred method of restoring internal lining, structural support, and external cover, all of which are governed by the extent of the nasal defect and availability of resources that can be used for the repair. Part Two represents the ?how to? section of the book. It provides detailed step-by step discussions of techniques used to design, dissect, transfer and refine flaps and grafts used in nasal reconstruction. It also reviews the prevention and management of complications. In Part Three, each chapter discusses a representative case or cases that demonstrate typical complications and limitations confronting all surgeons when reconstructing the nose. Designed so practitioners can add to their surgical repertoire with a thorough reading, or quickly consult the text aided by detailed labeling and hundreds of photographs, Principles of Nasal Reconstruction is an invaluable resource for otolaryngologists, head-and-neck surgeons, and plastic and reconstructive facial surgeons. About the Author Shan R. Baker, M.D., is Professor and Chief of the section of Facial Plastic and Reconstructive Surgery and Director of the Center for Facial Cosmetic Surgery in the Department of Otolaryngology Head and Neck Surgery, University of Michigan Health System. He has more than 30 years of surgical experience in reconstructing the nose.